The introduction of laminar flow to the design and optimisation of transport aircraft - Wilson, R. A. L. (Cranfield University, 1997)
A methodology has been developed to model the direct consequences of laminar flow technology on wing, empennage and nacelle surfaces. In particular two concepts were considered, namely Natural Laminar Flow (NLF) and Hybrid Laminar Flow Control (HLFC). The methodology was introduced into an existing numerical design synthesis for commercial transport aircraft, which was linked to a non-linear constrained optimisation code. This permitted the impact of laminar flow technology on the optimum aircraft configuration and Direct Operating Costs (DOC) to be assessed. Cont/d.